IHI ID 14 Rational opioid prescribing. (December 2018) - Ackerman, Adam; Scott Sussman, L; Doyle, Deirdre; Zematis, Christopher; Telford, Ryan; Williams, Anesta; Day, Christine; Ferrigno, Rockman; Hajdasz, David; Sotire, Bill; Fanning, Catherine; Cholewczynski, Connie
Abstract : Background: At Yale New Haven Health System, our default route for delivering parenteral opioids has previously been the intravenous route, which can increase the risk of hypotension, undesired central nervous system effects and potentially risk of addiction. A multidisciplinary team identified opportunities to modify how opioids are prescribed and administered to reduce the risk of these adverse effects. Objectives: To reduce the number of IV opioid doses administered to adult inpatients, emergency department and observation patients by 25% through the adoption of a system-wide opioid prescribing standard of practice. Methods: The redesigned practice includes four main principles: EPIC Optimization: The removal of the default route of intravenous delivery of parenteral morphine, hydromorphone and fentanyl orders for adult patients. Education of providers to consider prescribing non-opioid pain medications and/or oral opioids first with subcutaneous delivery as the preferred parenteral route. Education of clinical nurses to consider subcutaneous delivery as the preferred route when parenteral opioids are required and to have a questioning attitude if opioids are routinely prescribed via intravenous delivery. Development of patient education material to provide information about the preferred route for administration of opioids as oral and subcutaneous. Results: Please see the attachment with the data analysis. Conclusions: Our data suggests these interventions were helpful in reducing exposure to IV opioids while still providing effective pain control to hospitalized adults. The work of the team allowed patients to experience consistent delivery of pain medication, better pain control with decreased unwanted side effects.